An analysis of students' speaking anxiety in performing impromptu presentation - Maulida, Neng Hasna; Faridah, Didih; Tarwana, Wawan (Universitas Galuh, 2024)
This study explores speaking anxiety among students during impromptu presentations. Speaking anxiety, characterized by discomfort and excessive worry, can impact students' well-being and necessitate social support. The research investigates students’ experiences and influencing factors using a qualitative case study approach. Data was collected from 35 tenth-grade students at MAN 1 Garut through questionnaires and interviews. The questionnaire reached 35 participants from class X-4, while interviews involved 4 selected students. Results reveal that most students experience anxiety during impromptu presentations, manifesting as nervousness, mental withdrawal, and fear of making mistakes or negative judgments. To mitigate speaking anxiety, teachers can employ strategies such as improving body language and eye contact. The study emphasizes the importance of teacher support and motivation in helping students overcome anxiety. For students, the findings underscore the commonality of speaking anxiety and the need for more practice and mental health awareness when facing spontaneous presentations. Teachers' sensitivity and patience are key to addressing this issue effectively.